Performance evaluation of short-season cotton strains for the conditions of Minas Gerais state, Brazil - Penna, Julio Cesar Viglioni; Fallieri, Joel (Pesquisa Agropecuaria Brasileira, 1993)
The use of short-season cotton cultivars is of paramount importance in modern production systems which take in account the presence of the boll weevil. This research was designed to make an evaluation of the agronornic and fiber quality of 73 of such advanced lines under the two cotton conditions of the state of Minas Gerais, Brazil. In both locations tested, yields obtained on some of introduced types were similar and sometimes superior to the check varieties. As for the other traits, with the exception of a few lines presenting defects on fiber quality, the values found were considered within required standards. The direct utilization of such lines or their usage in breeding programs is discussed.